P‐3: A New LTPS Pixel Circuit for Compensating the Variation of TFT Characteristics and Alleviating OLED Degradation. Issue 1 (June 2015) - Hsu, Wei‐Chu; Wu, Pi‐Cheng; Jen, Ko‐Ruey; Lee, Chien‐Ya; Lin, Hong‐Shen; Chang, Lee‐Hsun; Lin, Yu‐Hsin
Abstract : In this paper, we have developed a pixel compensation circuit that utilizes six LTPS TFTs and one capacitor for AMOLED displays by voltage‐programmed method. The proposed pixel circuit can compensate the threshold voltage variation of TFT and extend OLED lifetime, which is able to show better compensation performances.